Arginine and nitric oxide synthase: Regulatory mechanisms and cardiovascular aspects - Lorin, Julie; Zeller, Marianne; Guilland, Jean-Claude; Cottin, Yves; Vergely, Catherine; Rochette, Luc (Molecular nutrition & food research, 2014)
l‐Arginine (l‐Arg) is a conditionally essential amino acid in the human diet. The most common dietary sources of l‐Arg are meat, poultry and fish. l‐Arg is the precursor for the synthesis of nitric oxide (NO); a key signaling molecule via NO synthase (NOS). Endogenous NOS inhibitors such as asymmetric‐dimethyl‐l‐Arg inhibit NO synthesis in vivo by competing with l‐Arg at the active site of NOS. In addition, NOS possesses the ability to be “uncoupled” to produce superoxide anion instead of NO. Reduced NO bioavailability may play an essential role in cardiovascular pathologies and metabolic diseases. l‐Arg deficiency syndromes in humans involve endothelial inflammation and immune dysfunctions. Exogenous administration of l‐Arg restores NO bioavailability, but it has not been possible to demonstrate, that l‐Arg supplementation improved endothelial function in cardiovascular disease such as heart failure or hypertension. l‐Arg supplementation may be a novel therapy for obesity and metabolic syndrome. The utility of l‐Arg supplementation in the treatment of l‐Arg deficiency syndromes remains to be established. Clinical trials need to continue to determine the optimal concentrations and combinations of l‐Arg, with other protective compounds such as tetrahydrobiopterin (BH4), and antioxidants to combat oxidative stress that drives down NO production in humans.